2001
DOI: 10.1042/bj3530441
|View full text |Cite
|
Sign up to set email alerts
|

An uncoupling protein homologue putatively involved in facultative muscle thermogenesis in birds

Abstract: The cDNA of an uncoupling protein (UCP) homologue was obtained by screening a chicken skeletal-muscle library. The predicted 307-amino-acid sequence of avian UCP (avUCP) is 55, 70, 70 and 46% identical with mammalian UCP1, UCP2 and UCP3 and plant UCP respectively. avUCP mRNA expression is restricted to skeletal muscle and its abundance was increased 1.3-fold in a chicken line showing diet-induced thermogenesis, and 3.6- and 2.6-fold in cold-acclimated and glucagon-treated ducklings developing muscle non-shiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 25 publications
5
57
0
5
Order By: Relevance
“…3B). Previous studies have shown that exposure to cold stress increased expression of avUCP [18,30,31] and avANT [18] gene transcripts in the skeletal muscle of birds. These results led to the hypothesis that expression of avUCP and avANT influence thermogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…3B). Previous studies have shown that exposure to cold stress increased expression of avUCP [18,30,31] and avANT [18] gene transcripts in the skeletal muscle of birds. These results led to the hypothesis that expression of avUCP and avANT influence thermogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Even so, no bird species thus far studied have been shown to possess distinct stores of BAT or a related type of thermogenic tissue [4,5]. However, the relatively increased expression of avUCP in cold-acclimated ducklings has been demonstrated [38], along with an increase of avANT and avUCP mRNA levels in the skeletal muscle of cold-acclimated chickens (4-6°C for 10-12 days) [11]. The present data demonstrate that avUCP expression in the skeletal muscle of cold-exposed chickens initially increased significantly and then decreased slightly, but, unlike UCP3 in rodent skeletal muscle, remained above basal levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of avUCP in cold-acclimated ducklings [24], chickens [25] and king penguins [26] has been demonstrated. Moreover, we also reported the negative correlation between avUCP content and mitochondrial superoxide production in chicken skeletal muscle during acute heat stress [27].…”
Section: Introductionmentioning
confidence: 96%
“…Although bird species have no distinct stores of BAT or a related type of thermogenic tissue [22,23], a new protein, named avian UCP (avUCP), which shares a 71-73% amino acid identity with both UCP2 and UCP3, was identified in chicken skeletal muscle [24,25]. Increased expression of avUCP in cold-acclimated ducklings [24], chickens [25] and king penguins [26] has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%